Analysis and interpretation of inflammatory fluid markers in Alzheimer’s disease: a roadmap for standardization - Brianne M. Bettcher; Fabricio Ferreira de Oliveira; Auriel A. Willette; Malgorzata M. Michalowska; Luiza Santos Machado; Binita Rajbanshi; Wyllians V. Borelli; Malú Gámez Tansey; Andréia Rocha; Vidyani Suryadevara; William T. Hu (Journal of Neuroinflammation)
Abstract Growing interest in the role of the immune response in Alzheimer’s Disease and related dementias (ADRD) has led to widespread use of fluid inflammatory markers in research studies. To standardize the use and interpretation of inflammatory markers in AD research, we build upon prior guidelines to develop consensus statements and recommendations to advance application and interpretation of these markers. In this roadmap paper, we propose a glossary of terms related to the immune response in the context of biomarker discovery/validation, discuss current conceptualizations of inflammatory markers in research, and recommend best practices to address key knowledge gaps. We also provide consensus principles to summarize primary conceptual, methodological, and interpretative issues facing the field: (1) a single inflammatory marker is likely insufficient to describe an entire biological cascade, and multiple markers with similar or distinct functions should be simultaneously measured in a panel; (2) association studies in humans are insufficient to infer causal relationships or mechanisms; (3) neuroinflammation displays time-dependent and disease context-dependent patterns; (4) neuroinflammatory mechanisms should not be inferred based solely on blood inflammatory marker changes; and (5) standardized reporting of CSF inflammatory marker assay validation and performance will improve incorporation of inflammatory markers into the biological AD criteria.